Pedagogical Strategies for the Transformation of Church Cultures An Examination of a Spiritual Leadership Development Program in Korean Immigrant Churches - Park, Hee-Kyu Heidi (2017)
How do we teach transformative ideas that challenge the conservative culture of a church? This paper explores the process by which a spiritual leadership education program that empowers lay women was conceptualized and implemented in the context of Korean immigrant Presbyterian churches. It pays special attention to the phases through which the program was developed in order to examine the challenges faced at each phase and the pedagogical strategies employed to counter those challenges. The insights gained through such adjustments will be explored in dialog with inspiration drawn from Septima Clark's Citizenship School work that paved the way for the civil rights movement and Bonnie Miller-McLemore's work on a maternal feminist epistemology.
Keywords: Pedagogy; Conservative; Leadership; Spirituality; Strategy; transformative; wholistic